Dynamic sex chromosome expression in Drosophila male germ cells - Mahadevaraju, Sharvani; Fear, Justin M.; Akeju, Miriam; Galletta, Brian J.; Pinheiro, Mara M. L. S.; Avelino, Camila C.; Cabral-de-Mello, Diogo C. [UNESP]; Conlon, Katie; Dell’Orso, Stafania; Demere, Zelalem; Mansuria, Kush; Mendonça, Carolina A.; et al. (Springer Nature, 2021)
Given their copy number differences and unique modes of inheritance, the evolved gene content and expression of sex chromosomes is unusual. In many organisms the X and Y chromosomes are inactivated in spermatocytes, possibly as a defense mechanism against insertions into unpaired chromatin. In addition to current sex chromosomes, Drosophila has a small gene-poor X-chromosome relic (4th) that re-acquired autosomal status. Here we use single cell RNA-Seq on fly larvae to demonstrate that the single X and pair of 4th chromosomes are specifically inactivated in primary spermatocytes, based on measuring all genes or a set of broadly expressed genes in testis we identified. In contrast, genes on the single Y chromosome become maximally active in primary spermatocytes. Reduced X transcript levels are due to failed activation of RNA-Polymerase-II by phosphorylation of Serine 2 and 5.